POTENSI WAKAF PRODUKTIF MENURUT PERSPEKTIF EKONOMI ISLAM : (Studi Kasus Pada Pondok Pesantren Ar- Raudlatul Hasanah Medan) - Nawawi, MUHAMMAD NAWAWI (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
The Productive Waqf Paradigm is a momentum as an effort to transform from traditional waqf management to professional waqf management to increase or increase the benefits of waqf. The management of productive waqf is the empowerment of waqf which is characterized by the main characteristics of the waqf management pattern that must be integrated, the principle of Nazir welfare that must be considered and the principle of transformation and responsibility. In this case, it is very important to link productive waqf management and development activities with Islamic boarding schools. Among the pesantren that can be considered successful in managing productive waqf is the Ar-Raudlatul Hasanah Islamic Boarding School. From the data obtained at the Islamic boarding school, it is known that the potential for productive waqf is in accordance with the perspective of Islamic economics. This type of research is qualitative. Data collection is in the form of in-depth interviews and is supported by literature studies. The data analysis method used is descriptive qualitative. Primary data sources are obtained directly from ustadz or teachers in Islamic boarding schools. and secondary data that researchers use in the form of documents, books, and journals. This study shows that the potential for productive waqf contained in the pesantren is in the form of Islamic Boarding School Owned Enterprises (BUMP). The management of productive waqf in Ar-Raudlatul Hasanah Islamic Boarding School is simple and traditional, namely: Waqf assets and businesses owned by Ar-Raudlatul Hasanah Islamic Boarding School are managed by Nazhir themselves and are traditional and voluntary. Then the line of business owned is a relatively simple form of business with minimal risk. The view of Islamic economics on productive waqf at the Ar-Raudlatul Hasanah Islamic Boarding School does not appear to violate the Shari'a. Overall, the line of business and the form of waqf management at the Ar-Raudlatul Hasanah Islamic Boarding School are in accordance with Islamic law.